2018
DOI: 10.1039/c7ra13148h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel (benzimidazolyl)isoquinolinols and evaluation as adenosine A1 receptor tools

Abstract: Mild, metal free aromatization of tetrahydroisoquinolinols. Synthesis of (benzimidazolyl)isoquinolinols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…5 If necessary, the initially formed tetrahydroisoquinolinol has to be subsequently oxidized. 6 More recently, it has been demonstrated that 3-hydroxyisoquinolines are available with significantly milder methods, for example, from B(C 6 F 5 )-/Co-catalyzed C−H bond activation reactions of imines with diazo compounds 7 or by a sequence of Ugi reaction and Pd-mediated Heck cyclization. 8 Herein, we present a novel synthetic route to 3-hydroxyisoquinoline derivatives that we incidentally discovered in failed attempts to functionalize halogenated benzo [b]quinolizinium derivatives 1b−e by nucleophilic substitution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 If necessary, the initially formed tetrahydroisoquinolinol has to be subsequently oxidized. 6 More recently, it has been demonstrated that 3-hydroxyisoquinolines are available with significantly milder methods, for example, from B(C 6 F 5 )-/Co-catalyzed C−H bond activation reactions of imines with diazo compounds 7 or by a sequence of Ugi reaction and Pd-mediated Heck cyclization. 8 Herein, we present a novel synthetic route to 3-hydroxyisoquinoline derivatives that we incidentally discovered in failed attempts to functionalize halogenated benzo [b]quinolizinium derivatives 1b−e by nucleophilic substitution.…”
mentioning
confidence: 99%
“…Thus, 3-hydroxyisoquinoline derivatives are available by the traditional cyclization methodsusually under harsh conditionswith the formation of the N-heterocyclic ring as the key step . If necessary, the initially formed tetrahydroisoquinolinol has to be subsequently oxidized . More recently, it has been demonstrated that 3-hydroxyisoquinolines are available with significantly milder methods, for example, from B­(C 6 F 5 )-/Co-catalyzed C–H bond activation reactions of imines with diazo compounds or by a sequence of Ugi reaction and Pd-mediated Heck cyclization .…”
mentioning
confidence: 99%
“…binding affinity to the A 1 AR. 54 Therefore, there still remains a need for fluorescent probes with marked subtype selectivity for the A 1 AR.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Singh et al designed fluorescent ligands based on a (benzimidazolyl)­isoquinolinol scaffold. However, these probes did not show measurable binding affinity to the A 1 AR . Therefore, there still remains a need for fluorescent probes with marked subtype selectivity for the A 1 AR.…”
Section: Introductionmentioning
confidence: 99%